Characterizing southern Baffin Island chert: A cautionary tale for provenance research. (December 2018) - ten Bruggencate, Rachel E.; Milne, S. Brooke; Fayek, Mostafa; Park, Robert W.; Stenton, Douglas R.; Hamilton, Anne C.
Abstract: The southern Baffin Island chert provenance project was initiated in 2007 to investigate the effects on Palaeo-Eskimo mobility and technological organization of the differential distribution of chert sources in this area of the eastern Arctic. Initial characterization of chert artifacts and sources by secondary ion mass spectrometry and inductively coupled plasma-mass spectrometry (ICP-MS) indicated exploitation of both local inland and exotic chert sources by Palaeo-Eskimo toolmakers. Subsequent reanalysis of chert artifacts by ICP-MS demonstrates that data acquired using these techniques cannot be directly compared. ICP-MS trace element data collected from two primary chert sources documented in 2013 showed promise for characterizing these sources. Subsequent reanalysis of source samples demonstrates that initial results were affected by contamination during sample preparation at an external laboratory and should not be used in future studies. Highlights: A technique for sourcing chert artifacts from southern Baffin Island is revisited. We show that SIMS and ICP-MS chert trace element data cannot be directly compared. We describe two newly-documented chert sources on southern Baffin Island. We present ICP-MS trace element data for these sources and tools from a nearby site. We show that this data was affected by contamination during sample preparation.